Paneth cells: histochemical and morphometric study in control and Solanum glaucophyllum intoxicated rabbits - Zanuzzi, Carolina Natalia (2008)
The intestinal epithelium has a critical roll in host defence. One specialised cell type involved in this function is the Paneth cell, which secretes many substances with antimicrobial properties in response to different stimuli. Under pathological conditions, changes in the Paneth cell number, morphology and location as well as in granule number, morphology and composition have been reported. In the normal animal, 1,25-dihydroxyvitamin D3 participates in the maintenance of mineral homeostasis, immunomodulation and cell proliferation and differentiation. Solanum glaucophyllum, a calcinogenic plant containing high levels of 1,25-dihydroxyvitamin D3, is responsible for a condition known as enzootic calcinosis in ruminants, characterised by loss of body condition and mineralization of soft tissues. Using and established rabbit model, this study analyses the changes that rabbit Paneth cells undergo during intoxication with S. glaucophyllum. Male New Zealand white rabbits were experimentally intoxicated with S. glaucophyllum for 15 or 30 days. Lectin, immunohistochemical and morphometric studies were carried out on Paneth cells from samples of jejunum. SBA, DBA and WGA lectins bound to Paneth cells-granules in both normal and intoxicated rabbits, with more heterogenity in the labelling of granules from intoxicated rabbits. Paneth cells in both groups were immunonegative for lysosyme. A time and dose-dependent increase in the size and number of Paneth cells was found in both intoxicated groups. We suggest that the changes described in these cells may be directly or indirectly induced by S. glaucophyllum intoxication.